Удмуртские народные мифы и легенды - Кралина Надежда Петровна (Удмуртия, 2016)
Экземпляры: ф.6 (20200921) / Инвентарный номер: 3481 И / Цена: / Сис.шифр: 82.3(2Рос=Удм)-6 / Авт.знак: У 30 / ГРНТИ: 17.71.91 / ББК: 82.3(2Рос=Удм)-6